Highly active and porous graphene encapsulating carbon nanotubes as a non-precious oxygen reduction electrocatalyst for hydrogen-air fuel cells. (August 2016) - Zamani, Pouyan; Higgins, Drew C.; Hassan, Fathy M.; Fu, Xiaogang; Choi, Ja-Yeon; Hoque, Md. Ariful; Jiang, Gaopeng; Chen, Zhongwei
Abstract: Heat treated iron-polyaniline-carbon – based non-precious metal catalysts represent a promising class of material to replace the platinum based ORR catalysts for PEMFC technologies. In the present research, we apply an ammonia treatment to tune the structure and activity of electrocatalysts derived from iron, polyaniline and carbon nanotubes (CNTs). By controlling the NH3 reaction conditions, we were able to tune the chemistry of nitrogen incorporation, including concentration and dopant type. The final catalyst had a robust morphology consisting of highly porous 2-D in-situ formed graphene-like structures that, along with the intermixed 1-D CNTs, were decorated with an abundance of nitrogen and iron species. The resultant surface chemistry led to impressive catalyst activity, with a half-wave potential of 0.81 V observed through half-cell testing and under H2 -air fuel cell testing, a current density of 77 mA cm −2 at 0.8 V was achieved, along with a maximum power density of 335 mW cm −2 . Graphical abstract: Highlights: NH3 was used to tune chemistry and activity of catalysts made from Fe, PANI and CNT. Catalyst was highly porous in-situ graphene mixed with CNT, decorated with N and Fe. Tuned chemistry led to impressive activity in half-cell and H2 -air fuel cell test.